Retorica del metodo scientifico o potere dell’incertezza? In aula come in laboratorio, costruire fiducia coltivando il dubbio - Govoni, Paola (Chimica nella Scuola, 2024)
How can we prepare the younger generation to effectively navigate various sources, whether they are books, social media, or ChatGPT, to find accurate and verified data and information? What strategies should we employ to instill confidence in their ability to engage in independent and exploratory learning, while cultivating skepticism towards jargon, authoritative figures, and ideological viewpoints? How can we adopt an approach to understanding reality that not only embraces uncertainties, doubts, and inevitable dead ends but also acknowledges the profound social and cultural complexities inherent in science? How can we liberate ourselves from obsolete narratives, including those associated with the rhetoric of the scientific method? In these times, questions seem to outweigh answers. Moreover, whether in the classroom or the laboratory, progressing through thoughtful inquiries is perhaps the most reliable path to navigate a reality that is increasingly unfolding in digital spaces.